Double-Loaded Liposomes Encasing Umbelliferone in Hydroxypropyl-β-Cyclodextrin Inclusion Complexes: Formulation, Characterisation and Investigation of Photoprotective Activity - Verekar, R.R.; Shaikh, Sh.B.M.; Rebelo, S.; Gurav, Sh.S. (Karagandy University of the name of academician E.A. Buketov, 2025)
Double-loaded liposomes are a system in which a drug is incorporated in the vesicle lipid layers after aqueous phase inclusion complexation to form a drug-in-cyclodextrin-in phospholipid vesicles complex. Umbelliferone (UMB) is a naturally occurring coumarin used as a photoactive agent because of its UV light absorption ability. In this study, the double loading (DL) technique was used to encapsulate “UMB in hydroxy propyl-β- cyclodextrin (HP-β-CD)-in-liposomes (UMB-CDLP)”. This led to the creation of “double-loaded liposomes encasing UMB in HP-β-CD (DL-UMB-CDLP)”, specifically developed to combine the power of solubilisation of HP-β-CD with the sustained release characteristics of phospholipid vesicles to improve solubility and dissolution profile. HP-β-CD and UMB inclusion complexes prepared by different methods were characterized by FTIR spectroscopy, DSC, saturation solubility, x-ray diffractometry, and scanning electron microscopy. DL-UMB-CDLP was developed using a thin film/lipid hydration method and a Box-Behnken design and was assessed by TEM, in-vitro diffusion studies and biological evaluation. The optimized DL-UMB-CDLP formulation demonstrated promising results, indicating the development of a stable composition. Animals treated with the DL-UMB-CDLP gel and exposed to the immediate irradiation protocol proved the UMB’s ability to protect against UV-induced oxidative damage based on the amount of antioxidant enzymes estimated to be present in rat skin.
Keywords: Umbelliferone; double-loaded liposome; inclusion complex; photoprotective activity; photoactive agent; irradiation protocol; drug-in-cyclodextrin; drug-in-phospholipid